2005
DOI: 10.1103/physrevb.71.075415
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of the meltinglike transition inLi13Na42andNa13

Abstract: Equilibrium geometries and the meltinglike transition of Na 13 Cs 42 and Li 13 Na 42 are studied by means of orbital-free density-functional-theory molecular dynamics simulations. A polyicosahedral structure is found to be energetically favored for Na 13 Cs 42 , with a core shell formed by Na atoms and complete segregation of Cs atoms to the cluster surface. Li 13 Na 42 adopts an amorphouslike structure, albeit with significant local polyicosahedral order, with the Na atoms preferentially occupying surface sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 54 publications
2
33
0
Order By: Relevance
“…Hristova et al 24 reported the GM structures of equiatomic K-Cs and Rb-Cs nanoalloys at the EP level. They observed a preference for p-Ih packing and core-shell segregation, in agreement with results by Aguado et al [12][13][14][15] for other alkali nanoalloys. A goal of the present study is to show that EP results are not quantitative for these systems as quantum electron shell effects play an important role.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Hristova et al 24 reported the GM structures of equiatomic K-Cs and Rb-Cs nanoalloys at the EP level. They observed a preference for p-Ih packing and core-shell segregation, in agreement with results by Aguado et al [12][13][14][15] for other alkali nanoalloys. A goal of the present study is to show that EP results are not quantitative for these systems as quantum electron shell effects play an important role.…”
Section: Introductionsupporting
confidence: 89%
“…For x = 19, the Li part is a double icosahedron formed by two interpenetrating 13-atom icosahedra. For x = 23 and x = 26, there are respectively three and four interpenetrated Li 13 icosahedra.…”
Section: A Model Potential Structuresmentioning
confidence: 99%
“…For some compositions, we indeed observe poly-decahedral packing, obtained by interpenetrating several 13-atom decahedra. For x = 20, the lithium subsystem is formed by two interpenetrated Li 13 decahedra, while three decahedra form the core of the highsymmetry structure observed for x = 25. Close to the stability limit of the decahedral family, we observe a close competition of poly-decahedral and pIh core motifs.…”
Section: B Structures Of LI X Cs 55−xmentioning
confidence: 99%
“…The same preference for polyicosahedral and/or polytetrahedral packing has been independently obtained by Calvo and Yurtsever 28 and Doye and Meyer 29 for mixed LJ clusters and by Aguado and López for binary and ternary mixtures of alkali metals. 35,36 Anti-Mackay overlayers are not specially stable for homogeneous clusters because of the associated bond strain, but they are very stable in those mixtures which present ͑a͒ a sufficiently large size mismatch and ͑b͒ a lower surface tension of the atomic species with larger radius. In this case, both core ͑Ni/ Na/ Ar͒ and surface ͑Ag/ Cs/ Xe͒ atoms may have interatomic distances close to optimal in the polyicosahedral structure, which explains its stabilization.…”
Section: Introductionmentioning
confidence: 99%